(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
In the article the problem of higher education in the scientific and technical progress and restructuring of the socio-economic system in Ukraine. Outlined the severity of the situation on Ukrainian language in secondary schools and its use in all spheres of public life. It has been suggested scientists about the imperfections of language programs in disciplines shortage of skilled professionals, which ultimately leads to poor language training high school graduates, inability logically, consistently, coherently express their thoughts. Researchers are concerned about the lack of programs themes which help nurture national and universal tradition of rhetoric that are important personality traits – a full member of society. That’s why higher education has gained urgency the problem of introducing new trends, content, methods, forms, preparing students for professional careers. Development of communicative culture of students - one of the urgent problems the teacher of high school. Ukrainian professional speech that is in its infancy, regimentation inherent features that define more cultural level of oral and written business communication and specificity of professional broadcasting is to serve the areas of industrial relations, communication needs between one profession. Because the course “Ukrainian language (for professional purposes)” in higher education not only eliminates gaps in learning the Ukrainian language in secondary schools in Ukraine, but also promotes proper professional training and intellectual level. He continued formation of national linguistic identity, broadens language competence of future specialist in the professional field, as the focus is shifting from the traditional task - assimilation of information about literary norms of the Ukrainian language - on the skills of professional communication, professional mastering features of language, the culture of the language. Shaping the future professionals skills and abilities fluency in Ukrainian literary language in the professional field, the course content is caused by a variety of tasks designed to ensure that students are properly used according to the language means and communicative needs as best guided in the speech process.